Eco Beach Cleaner - Amit Kumar Yadav; Animesh Singh; M. A. Murtaza; Ajendra Kumar Singh (International Journal of Engineering and Management Research, 2018)
Trash and litter left on beaches can endanger the life of coastal animals, like turtles and birds, and also damage tourism industries by diminishing the natural beauty of beaches. To solve this problem, most coastal areas employ manual labor, volunteer work, or large zambonini-like machines to pick of trash. However, these operations are very expensive and time-consuming. In order to efficiently stop the increasingly negative impact of trash debris on coastal ecosystems, forms of mechanized, autonomous trash collection and disposal need to be utilized. Developing a robot that can transverse sandy terrain, pick up small trash debris, dispose of contained trash debris, and avoid large objects and the ocean all while functioning autonomously presents a variety of technical challenges. The invention is predicated upon the later developed concept of raking or combing the sand to a degree of continuity and thoroughness that will assure removal of not only larger sized debris, but also the bulk of smaller pieces such as broken glass, nails and the like, without necessitating or involving the removal or displacement with the debris, of any consequential quantities of the beach sand itself. This paper present the controlling and monitoring of the solar power device which is capable of picking up the miscellaneous litter which accumulates on the beach and collects all the litter after filltering the sand to a self attached trash box.